Komparasi Kompetensi Keguruan Mahasiswa pada Program Kampus Mengajar dan Praktek Lapangan Kependidikan - Nurfadhilah, Hilya; Alfurqan, Alfurqan (An-Nuha, 2025)
The Teaching Campus program of MBKM serves to introduce students to teaching experiences and plays a role in improving students' literacy and numeracy skills. Students who take part in the teaching campus will get a conversion of 20 credits, one of the courses that can be converted is Educational Field Practice. This study aims to determine whether there is a significant difference in the ability of teacher competence for those who take part in the Teaching Campus Program with those who take part in Educational Field Practices in the 2020 Islamic Religious Education Class. The method used is a quantitative method with a comparative approach. Data sources were taken from seventy-nine respondents through questionnaires. The data were analyzed using the independent sample T-test. Data validity techniques use validation tests and reliability tests. The results of the analysis show that there is a significant difference in the ability of teacher competence for those who follow the Teaching Campus with Educational Field practice. Where the average value of the ability of teacher competence of Educational Field Practice is higher than those who follow the Teaching Campus program.